Compositional Variations in the Vicinity of the Lunar Crust‐Mantle Interface From Moon Mineralogy Mapper Data. Issue 12 (27th December 2018) - Martinot, M.; Flahaut, J.; Besse, S.; Quantin‐Nataf, C.; van Westrenen, W.
Abstract: Moon Mineralogy Mapper spectroscopic data were used to investigate the mineralogy of a selection of impact craters' central peaks or peak rings, in order to characterize the lunar crust‐mantle interface, and assess its lateral and vertical heterogeneity. The depth of origin of the craters' central peaks or peak rings was calculated using empirical equations, and compared to Gravity Recovery and Interior Laboratory crustal thickness models to select craters tapping within +10/−20 km of the crust‐mantle interface. Our results show that plagioclase is widely detected, including in craters allegedly sampling lower crustal to mantle material, except in central peaks where Low‐Calcium Pyroxene was detected. Olivine detections are scarce, and identified in material assumed to be derived from both above and below the crust‐mantle interface. Mineralogical detections in central peaks show that there is an evolution of the pyroxene composition with depth, that may correspond to the transition from the crust to the mantle. The correlation between High‐Calcium Pyroxene and some pyroxene‐dominated mixture spectra with the location of maria and cryptomaria hints at the existence of lateral heterogeneities as deep as the crust‐mantle interface. Plain Language Summary: This study surveys the mineralogy of 36 lunar impact craters scattered across the lunar surface. All these craters present a central peak or peak ring, inherited from the impact, where material from depth was brought up to the surface. According to our calculations, these craters should sample material originating from as deep as the interface between the crust and the mantle (+10/−20 km). We make use of visible near‐infrared spectroscopy (we investigate the light that is reflected from the lunar surface) in order to infer the central peaks compositions. We detected several minerals within the craters, including plagioclase, olivine, spinel, and pyroxene. An evolution of the composition of pyroxene (from High‐Calcium to Low‐Calcium) is observed with depth. We also demonstrate the presence of lateral heterogeneities within the crust and at the crust/mantle interface. Key Points: Plagioclase is widely detected in the central peaks of craters allegedly sampling the lower crust or mantle, except where LCP is observed Lateral heterogeneities at the crust‐mantle interface and a pyroxene compositional evolution with depth (from HCP to LCP) were observed This study's mineralogical observations support the GRAIL crustal thickness model 1 better than the model 3